(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Coronavirus disease (COVID-19) has impacted many nations' health care and their economic growth within no time. This Pandemic situation demands a safe and cost-effective treatment as early as possible to prevent any further suffering. To clinically evaluate the safety and efficacy of T-AYU-HM Premium Tablets (600 mg) and onion steam inhalation in mild to moderate COVID-19 patients. The trial is an open-label, Single-arm study conducted in mild to moderate level coronavirus patients. 30 participants infected by the coronavirus enrolled for the study, on providing informed consent. AYUSH standard mark anti-sickling tablet T-AYU-HM Premium 600mg twice a day and onion steam inhalation once every morning once for 21 days was prescribed to the patients along with strict home quarantine instructions. Both clinical and pathological changes recorded on the baseline, 5th, and 21st day of the trial. Any adverse events reported by the patients and those observed by the principal investigator recorded. All the patients recovered clinically, and no untoward effects observed during this trial period. A significant reduction (p < 0.05) observed in the pathological parameters like C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and lactate dehydrogenase (LDH). The oxygen saturation (SpO2) level sustained within normal limits during the treatment period suggesting that further complications and hospitalization evaded. The impact of the treatment regimen T-AYU-HM Premium and onion steam inhalation on clinical and pathological parameters suggest that it is safe and indicate its potential candidacy in the treatment of COVID-19.